PEMANFAATAN BATU BERSILIKA, SILANE, DAN VINYL SILANE SEBAGAI PENGISI BAHAN ISOLASI RESIN EPOKSI UNTUK ISOLATOR LISTRIK - Moh Toni Prasetyo; Solechan Solechan (Universitas Muhammadiyah Semarang, 2017)
One of the insulating polymer in high voltage air insulation materials is epoxy resin because it has several advantages. However, has a degradation of the surface due to environmental pollution. This research was conducted on resin epoxy by comparison of MPDA, DGEBA, and filler (stone and silane) with a percentage value of 10%; 20%; 30%; 40% and 50%, sample size 120 x 50mm. vinyl silane is mixed as a coupling agent of composite materials. Vacuum method to left out void. Research was done in laboratory according to standard IEC 587: 1984. High voltage electrodes were connected to high voltage AC generator 3.5 KV. The ground electrode was connected to oscilloscope for measuring the leakage current. The effect of variation were analyzed. From the results of the research, the composite are categorized as hydrophobic and partially wetted. The increase concentration of filler caused the increase in contact angle, slow down the aging on the surface of insulating material. Concentration value of filler that had the optimal performance was 40%. Keywords: Angle of contact, epoxy resin, hydrophobik, vacuum composite, vinyl silane